Sex and gender differences in caregiving burden experienced by family caregivers of persons with dementia: a systematic review protocol. Issue 8 (13th August 2018) - Xiong, Chen; Biscardi, Melissa; Nalder, Emily; Colantonio, Angela
Abstract : Introduction: While much is known about caregiving burden and its consequences on both caregivers and care recipients, reports on the sex and gender differences that may be present among family caregivers of persons with dementia (PWD) are lacking. Attention to and a synthesis of these sex and gender distinctions have direct implications on the planning and development of health services for this population. The current protocol outlines a strategy for a systematic review of the current evidence to identify and synthesise sex and gender distinctions in caregiving burden experienced by family caregivers of PWD. Methods and analysis: A comprehensive search strategy for studies that examine the sex and gender differences in caregiving impacts and experiences has been developed in collaboration with an information specialist at a university. All peer-reviewed English language studies on adult family caregivers of PWD, published from January 2007 to September 2017, found through Medline, Embase, PsycINFO, Cumulative Index to Nursing and Allied Health Literature and bibliographies of identified articles, will be considered eligible. Study quality will be assessed using the Critical Appraisal Skills Programme checklists. Ethics and dissemination: As the first systematic review of its kind that focus on sex and gender differences in caregiving burden, findings will be relevant for healthcare practitioners and researchers who can better prescribe and develop interventions and technologies to better address the specific challenges and burden experienced by male and female family caregivers of PWD. Moreover, given that more than half of family caregivers are females; these sex and gender differences will also be pertinent to policy-makers when evaluating and planning of our healthcare systems to better meet the needs of this population. Trial registration number: CRD42018070032.